7. Nacionalna konferenca o varnosti v lokalnih skupnostih : Policijsko delo v skupnosti in zagotavljanje varnosti v lokalnih skupnostih: konferenčni zbornik (University of Maribor Press, 2021)
7th National Conference on Local Safety and SecurityCommunity Policing and Provision of Safety and Security in Local Communities: Conference Proceedings. Conference proceedings comprise peer-reviewed papers presented at the 7th National conference on safety and security in local communities, which took place in Podčetrtek in November 2019. Safety and security in local communities remains the main topic of the annual conference, however, this time the focus was on community policing and their cooperation with local communities. Papers are the result of research within the research programme Safety and security in local communities – comparison of rural and urban environments, conducted at the Faculty of Criminal Justice and Security, University of Maribor and cooperation with practitioners. Papers focus on various aspects of safety and security in local communities, namely on policing and the impact of covid-19, practical aspects and coordination at various levels, philosophy, strategies, organisational factors, tactics and methods, as well as aspects of community policing development in recent decades. In addition to the presentation of the development of community policing in Slovenia, the papers present a good basis for a reflection on the development of community policing in the future.